PENGARUH MAKROPRUDENSIAL DAN MIKROPRUDENSIAL TERHADAP HARGA SAHAM - Saputri, Oktoviana Banda (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
The existence of Islamic banking in Indonesia still not as advanced the spirit of Islamic economic life significantly. Based on Indonesia Stock Exchange data, PT Bank Panin Dubai Syariah, Tbk (PNBS) has the first Islamic banking to register on the stock exchange on January 15, 2014. This reasearch’s aim to analyze indicators that have a greater effect on changes in stock price index . There are six independent variables that are predicted to affect the PNBS stock price. Based on the macro indicators of inflation, exchange rate and BI 7day repo rate, while micro indicators consist of total assets, DPK growth, and the amount of profit (loss). Data collection using secondary data obtained from several sources. By using time series regression analysis followed by the ARCH model, while in the short term testing using the ECM method. Based on results, the short-term output is closer to theory and hypothesis compared to long-term testing and macroprudential indicators have a greater effect on the PNBS stock price index than macroprudential indicators. This study provides recommendations that improving financial performance is very important for the Islamic banking industry.